The Determinants Of Profit Growth In Manufacturing Companies Food And Beverage Sub Sector Listed On The Indonesia Stock Exchange - Siti Rukoyah; Rini Syahril Fauziah; Elita Melani (Westscience Press, 2023)
This study aims to determine which variables impact the profit growth drivers of manufacturing businesses listed on the Indonesian Stock Exchange. Profit growth is the dependent variable in this study, whereas the current ratio, debt-to-equity ratio, and total asset turnover are the independent factors. The study object is based on data from 26 manufacturing businesses in the food and beverage sub-sector listed on the Indonesia Stock Exchange, with five manufacturing companies selected and sampled from that population throughout the 2017-2019 timeframe. The research was analyzed using SPSS and included the classical assumption test, linear regression analysis, t-test, f test, and coefficient of determination.